Changes in agricultural land use for watermelons and melons in the Middle Euphrates region between 1986 and 2022 (The International Journal of Educational Sciences and Arts, 2026)
Geographical phenomena in general, and agricultural phenomena in particular, are subject to constant change, influenced by factors of place and time. The Middle Euphrates region is one of the most important agricultural regions in Iraq due to the availability of natural and human resources for agriculture. These resources are also variable and unstable, which has been reflected in changes in agricultural land use, particularly the use of agricultural land for watermelons and melons. Due to the economic importance of these two crops، this study was conducted to reveal the extent of change in the area planted, production, and productivity of these crops for the period 1986-2022. This helps to understand the direction, magnitude, and spatial and temporal variation of change in the region. It was found that there was an absolute negative change in the area planted with watermelons، amounting to (20,883 dunums), and an absolute positive change in the area planted with melon crops of (1,772 dunums). As for the change in production, there was an absolute negative change for watermelons production (27,721 tons), while there was an absolute positive change for melon production (19,090 tons). As for the change in productivity per dunam of watermelons and melon crops, there was a positive change amounting to (10,037 and 7,487 kg/dunam، respectively). The study concluded with a set of recommendations, the most important of which were the use of modern irrigation techniques for both crops and the adoption of appropriate agricultural policies to support farmers and crop production، enabling the expansion and continuation of their cultivation.
Keywords: Change; Agricultural Land Use; Middle Euphrates